2007
DOI: 10.1103/physrevlett.98.136804
|View full text |Cite
|
Sign up to set email alerts
|

Surface Double Layer on (001) Surfaces of Alkali Halide Crystals: A Scanning Force Microscopy Study

Abstract: In this Letter we consider the surface double layer on (001) surfaces of UHV cleaved and annealed alkali halide crystals (KCl, NaCl), which we studied with dynamic scanning force microscopy and Kelvin probe force microscopy. Kelvin images show bright and round patches at corner sites and steps. Images with atomic resolution always show kinks at the latter step sites. Our findings are in perfect agreement with the long-standing picture that, due to the presence of divalent impurity ions, the surface carries a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 33 publications
7
81
1
Order By: Relevance
“…Recently, a comparison between calculated and measured data has shown that on the ͑001͒ surface of KBr, site-specific force-distance data can be used to identify the charge of the imaging ion on the tip. 6,13 Calculating force differences between two sites allow to eliminate long-range forces due to residual surface charge 14 and due to the van der Waals interaction. Similarly, it has been proposed that an analysis of the force as a function of distance should allow to identify the charge of the imaging ion on the tip for the ͑001͒ surface of NaCl, 15 a surface that has been recently studied with threedimensional force measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a comparison between calculated and measured data has shown that on the ͑001͒ surface of KBr, site-specific force-distance data can be used to identify the charge of the imaging ion on the tip. 6,13 Calculating force differences between two sites allow to eliminate long-range forces due to residual surface charge 14 and due to the van der Waals interaction. Similarly, it has been proposed that an analysis of the force as a function of distance should allow to identify the charge of the imaging ion on the tip for the ͑001͒ surface of NaCl, 15 a surface that has been recently studied with threedimensional force measurements.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that atomic interaction increases due to the low coordination of the step ions [21], forming an Ehrlich-Schwoebel-like barrier [22]. Furthermore, trapped local charges have been observed near step edges [23,24].…”
mentioning
confidence: 99%
“…However, SFM allows imaging the complete topography including the height of objects on surfaces as has been shown before on the (001) surfaces of pure alkali halide crystals [22,23]. Furthermore, SFM in its dynamic mode allows true atomic resolution imaging [24], which can be successfully applied on the (001) surfaces of alkali halides [25]- [27] even in the presence of defects [1,28]. Additionally, the Kelvin modulation technique can be implemented, which yields useful information about the surface charge distribution on insulator surfaces [28]- [30].…”
Section: Introductionmentioning
confidence: 90%
“…In the case of an insulator, the work function between the tip and the metallic sample holder in the presence of the insulator is measured [76], which is, however, strongly modified by surface charges. In most cases, the surface charge distribution determines the Kelvin contrast [28]. The Kelvin modulation is applied during the normal topography imaging so that a topography and a Kelvin image (U dc,0 ) are obtained at the same time in one Kelvin measurement.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation